Measurement of an elongation of the pion source in Z decays - Dova, María Teresa (1999)
We measure Bose-Einstein correlations between like-sign charged pion pairs in hadronic Z decays with the L3 detector at LEP. The analysis is performed in three dimensions in the longitudinal center-of-mass system. The pion source is found to be elongated along the thrust axis with a ratio of transverse to longitudinal radius of 0.81±0.02+0.03−0.19.